EFFECTS OF PRINCIPALS’ SUPERVISION PRACTICES ON TEACHERS’ JOB PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN KATHIANI SUB-COUNTY - Mutua, Mary Mbithe; Kimiti, Richard Peter; Koech, Peter Kibet (Scholarly Research Journal for Humanity Science & English Language, 2022)
Supervision is the process of administration which involves the push to manage everyday activities of people working in the school system. Principals facilitate the implementation of the various sets of instructional activities geared towards an effective and qualitative educational system that improve the teaching-learning situation. The objective of the study was to examine the effect of principals’ supervision practices on teachers’ job performance in public secondary schools in Kathiani SubCounty, Kenya. The study utilized a descriptive research design. The target population consisted of 32 principals and 107 teachers who were drawn from the 32 public secondary schools in the SubCounty. Questionnaires and interviews were used as data collection instruments. The study findings show that principals’ supervision practices and teachers’ job performance have a positive and significant relationship. The principal supervision practices that improved teacher job performance are supervision of teachers work plan, monitoring teachers on punctuality to class, tracking teachers on preparation of instructional documents and, overseeing teachers on matters related to curriculum and teaching methods. The study recommends that principals should ensure that they create a friendly environment so that they have a great relationship with the teachers which would boost communication both top-down and bottom-up. This would ensure that teachers are free to raise any underlying issues and also give insights to improve their relationship.
Keywords: Job performance; public secondary schools and supervision practice